2014
DOI: 10.12816/0006071
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Activities of Arabic and Indian Origin Salvadora Persica Root Extract on Diabetic Rats with Histopathology of Their Pancreas

Abstract: Objective: To evaluate hypoglycemic and hypolipidemic effects of Salvadora persica aqueous extracts on streptozotocininduced diabetic rats by measuring fasting blood glucose levels, lipid profiles and histopathological analysis of pancreas. Materials and Methods:Experimental Diabetes was induced by single intraperitoneal injection of streptozotocin (60 mg/kg) to albino Wistar rats. Salvadora persica extracts were administered orally at 250 and 500 mg/kg dose levels for 21 days. Glucose tolerance test (GTT) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In the treatment groups, it seems, inhibitory action of insulin on 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductase (HMG‐CoA reductase) is associated with lesser cholesterol generation and improvement of LP, but doubtful. Our results are in agreement with the results of Khan et al and Rabey et al In all the investigations mentioned above, hydroalcoholic extract of S. persica revealed antihyperlipidemic activity in diabetic rats. In our study, we found that the effects of ASP extract were more than the ethyl acetate and hydroalcoholic extracts.…”
Section: Discussionsupporting
confidence: 94%
“…In the treatment groups, it seems, inhibitory action of insulin on 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductase (HMG‐CoA reductase) is associated with lesser cholesterol generation and improvement of LP, but doubtful. Our results are in agreement with the results of Khan et al and Rabey et al In all the investigations mentioned above, hydroalcoholic extract of S. persica revealed antihyperlipidemic activity in diabetic rats. In our study, we found that the effects of ASP extract were more than the ethyl acetate and hydroalcoholic extracts.…”
Section: Discussionsupporting
confidence: 94%
“…The cytotoxic effects of S. persica plant on human gingival fibroblast cells has been reported by Balto et al (2014) . Khan et al (2014) have reported the hypoglycemic and hypolipidemic activities of its root extracts on diabetic rats. S. persica is a facultative halophyte which is adapted to survive under various adverse environmental conditions ranging from deserts to heavy soil, non-saline to highly saline soil, and dry regions to marshy and waterlogged areas ( Reddy et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of S.persica extract decreased blood glucose significantly in the first week of treatment, and this was more evident in the third week for both doses used [ 49 ]. Salvadora persica contains β -sitosterol with reported antioxidant effects, and many amides have been reported as having an insulin secretagogue effect and α -glucosidase-inhibition activity [ 49 ].…”
Section: Medicinal Plants With Potential Antidiabetic Activity In mentioning
confidence: 99%